2012
DOI: 10.1002/smll.201200864
|View full text |Cite
|
Sign up to set email alerts
|

From Bare Metal Powders to Colloidally Stable TCO Dispersions and Transparent Nanoporous Conducting Metal Oxide Thin Films

Abstract: Cataloged from PDF version of article.A simple, green, robust, widely applicable, multi-gram and cost-effective 'one-pot' synthesis of aqueous dispersions of colloidally stable 3-6 nm TCO NPs using bare metal powder precursors is described, and their utilization for making TCO high surface area nanoporous films is also demonstrated, which speaks well for their usage in a wide range of possible processes and devices. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Lattice expansion is not new and has been observed in many doped metal oxides. 27 Basically, doping of impurity ions into nanocrystals will not only alter the lattice parameters and electronic structure but also lead to novel properties. For instance, CeF 3 :Eu 3+ nanocrystals exhibited a lattice contraction, distorted lattice symmetry, and enhanced luminescent properties via Gd 3+ doping.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice expansion is not new and has been observed in many doped metal oxides. 27 Basically, doping of impurity ions into nanocrystals will not only alter the lattice parameters and electronic structure but also lead to novel properties. For instance, CeF 3 :Eu 3+ nanocrystals exhibited a lattice contraction, distorted lattice symmetry, and enhanced luminescent properties via Gd 3+ doping.…”
Section: Resultsmentioning
confidence: 99%
“…Transparent conductive oxides (TCOs) are considered as a technologically important class of materials because of their unique combination of good electrical conductivity, high chemical stability, visible light transparency and near infrared light reectance/absorption. [1][2][3][4][5][6][7][8][9] For example, TCOs such as antimony-doped tin oxide (ATO), 10 tin-doped indium oxide (ITO), 4 uorine-doped tin oxide (FTO), 11 aluminum-doped zinc oxide (AZO), 12 gallium-doped zinc oxide (GZO), 13 and indiumdoped zinc oxide (IZO) play a critical role in photovoltaic cells, 2,14 energy-efficient windows, at panel displays, light emitting diodes (LED) and liquid crystal display (LCD). Among them, ZnO based materials have recently gained more and more interests owing to both the low price and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[21] We found that by replacing the original solvent of water with n-butanol, and by reducing the metal concentration to 0.1 M, the diameter of the dispersed NPs measured using dynamic light scattering (DLS) was reduced from ∼5 nm to 0.7 ± 0.1, 1.6 ± 0.4, 1.0 ± 0.2, and 0.9 ± 0.4 nm for MoO 3 , WO 3 , NiO x , and CoO x , respectively ( Table I). The surfactant-free NP suspensions exhibit different colors arising from band gap and/or intraband d-d transitions of the metal oxides [ Fig.…”
Section: Np and Film Propertiesmentioning
confidence: 97%